Making Meaning of the Retirement Portfolio and its Impact on Learning in the Third Age - Darcia L. Simpson; Elice E. Rogers; Catherine A. Hansman; Jonathan E. Messemer (Adult Education Research Conference, 2014)
This roundtable examines relevant literature concerning the impact of one’s retirement portfolio and the economic self-sufficiency essential for learning and living in the Third Age of life. Third Agers are conceptualized as active retirement aged individuals, in good health with possibly 20+ years of life ahead of them.